Pengaruh Jumlah Dewan Direksi, Persentase Saham Publik, Leverage, Dan Ukuran Perusahaan Terhadap Manajemen Laba - Ruli Wulandari; Ade Kemala Jaya (Jurnal Media Akuntansi (Mediasi), 2023)
ABSTRACT The aim of this research is to examine the influence of board of directors' composition, leverage, and firm size on the practise of earnings management within organisations. The research combines four distinct independent variables and one corresponding dependent variable. The research employed a quantitative methodology. The sample size for this study consisted of 96 firms. The research utilised a sample including 37 manufacturing companies operating in the basic materials sector, which were registered on the IDX during the period of 2021-2022. The documentation method was employed to gather relevant data for the study. The study results indicate that many factors, including the number of board of directors, percentage of public shares, leverage, and business size, combined have a significant impact on the value of f-count. This impact is shown to be bigger than the crucial value of f-table. The estimated f-value of 5.171 above the cutoff value of 2.50. The t-test findings done by the board of directors suggest that the computed t-value of 3.222 is more than the crucial t-value of 1.66724. The statistical analysis reveals that the correlation between the percentage of public shares and earnings management is not statistically significant. This is shown by the p-value of 0.280, which exceeds the specified significance threshold of 0.05. In addition, the variable of leverage was subjected to a t-test, resulting in a t-value of -3.348. This t-value above the crucial t-value of 1.66724, suggesting the presence of statistical significance. The calculated p-value of 0.001 is below the specified significance threshold of 0.05. The results of the t-test on company size show a calculated t-value of 0.367 < t-table 1.66724 and the results of the significance value of company size are 0.715 > 0.05. Keywords: Board of directors, public stock, Leverage, Company size, and Earnings management. ABSTRAK Tujuan dari riset ini adalah untuk mencari tahu dampak jumlah dewan direksi, leverage, dan ukuran perusahaan pada manajemen laba perusahaan. Riset ini menggabungkan empat variabel independen dan satu variabel dependen. Riset ini memakai metode kuantitatif. Populasi untuk riset ini sebanyak 96 perusahaan. Riset ini memanfaatkan sampel sebanyak 37 perusahaan manufaktur sektor basic material yang terdaftar di BEI periode 2021-2022 dengan metode dokumentasi. Dari hasil penelitian dapat diamati bahwa variabel-variabel seperti jumlah dewan direksi, persentase saham publik, leverage, dan ukuran perusahaan secara bersama-sama mempengaruhi dengan nilai f-hitung > f-tabel yakni 5,171 > 2,50. Berdasarkan uji t dewan memperlihatkan nilai t-hitung 3,222 > t-tabel 1,66724. Tidak ada dampak persentase saham publik terhadap manajemen laba yang terlihat dari tidak signifikannya persentase saham publik dengan nilai signifikansi 0,280 > 0,05. Selanjutnya uji t yang dilakukan terhadap variabel leverage menunjukkan nilai t-hitung -3,348 > 1,66724 yang menunjukkan signifikansi statistik. Hal ini juga diperkuat oleh nilai p-value sebesar 0,001 < 0,05. Uji t yang dilakukan terhadap ukuran perusahaan menghasilkan nilai t-hitung 0,367 < t-tabel 1,66724. Selain itu, nilai signifikansi ukuran perusahaan sebesar 0,715 > 0,05. Kata kunci: Dewan direksi, saham public, Leverage, Ukuran Perusahaan, dan Manajemen Laba.